New Bilbilian (early Cambrian) archaeocyath-rich thrombolitic microbialite from the Láncara Formation (Cantabrian Mts., northern Spain) - Perejón, A.; Moreno-Eiris, E.; Bechstädt, T.; Menéndez, S.; Rodríguez-Martínez, M. (Journal of Iberian Geology, 2012)
Recent palaeontological and microfacies studies carried out on the Láncara Formation (early Cambrian) provide evidence for an interesting, previously undescribed association of archaeocyaths (Salce locality) and microbialites (Salce and Barrios de Luna localities). The archaeocyathan assemblage consists of Archaeocyathus laqueus (Vologdin, 1932) and Pycnoidocyathus erbiensis (Zhurav leva , 1955), indicating an early Bilbilian age (Stage 4, Series 2, Cambrian) for these materials. The analysis of the upper part of the lower member has allowed differentiation of eleven carbonate facies that have been grouped into: i) non-skeletal grain packstone-grainstone, ii) fenestral mudstone-packstone, iii) heterolithic stylonodular facies, iv) microbialites, v) bioclast-intraclast packstone-grainstone. Archaeocyaths occur reworked in stylonodular facies as well as forming small archaeocyaths-thrombolitic patches (centimetre-scale). The archaeocyath-rich thrombolitic microbialites from Salce were developed in very shallow subtidal conditions surrounded by other microbialites and small lenticular intertidal bars in the inner ramp. Toyonian biostratigraphic and paleobiogeographic analyses have also been carried out. After the comparison with Toyonian archaeocyathan rich facies from Gondwana, it has become evident that the early Cambrian record from the Cantabrian Mountains provides the richest generic assemblage from Gondwana for Toyonian time.